Algerian French Literature Between Praise And Blame Of Cultural Phenomena - Rahmani, Mokhtaria (جامعة الوادي - University of Eloued, 2022)
Literature and society cannot be dissociated from each other as one nurtures the other, molding, thereby, patters of expression. Through its different genres, it helps to unveil the existing currents of thought which it either praises the merits or denounces the anomalies. The present paper addresses the exploration of the binary role of Algerian literature, precisely novels, in picturing acclaim and castigation vis-à-vis cultural modes and dogma. To carry out this investigation, a descriptive-analytical method canvasses three elements, namely the meaning of literature and its place in society, secondly the different uses of praise by novels and the parameters grounding it, and finally the cases of blame and the actors generating it. The findings concede that acclaim occurs in situations where the author feels the need to paint the virtues of a cultural trait of his society, whether it is related to customs, traditions, language, or its heritage of folk stories. The results indicate also that blame occurs generally when the author feels aversion towards certain forms of his culture which he strongly needs to denounce and suppress.
Articl
Keywords: literature ; praise ; blame ; ideology ; welfare